2013
DOI: 10.1021/ic401119p
|View full text |Cite
|
Sign up to set email alerts
|

Counteranion and Solvent Assistance in Ruthenium-Mediated Alkyne to Vinylidene Isomerizations

Abstract: The complex [Cp*RuCl((i)Pr2PNHPy)] (1) reacts with 1-alkynes HC≡CR (R = COOMe, C6H4CF3) in dichloromethane furnishing the corresponding vinylidene complexes [Cp*Ru═C═CHR((i)Pr2PNHPy)]Cl (R = COOMe (2a-Cl), C6H4CF3 (2b-Cl)), whereas reaction of 1 with NaBPh4 in MeOH followed by addition of HC≡CR (R = COOMe, C6H4CF3) yields the metastable π-alkyne complexes [Cp*Ru(η(2)-HC≡CR)((i)Pr2PNHPy)][BPh4] (R = COOMe (3a-BPh4), C6H4CF3 (3b-BPh4)). The transformation of 3a-BPh4/3b-BPh4 into their respective vinylidene isome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 73 publications
3
33
0
Order By: Relevance
“…These values correspond well with a recent theoretical report for a similar reaction in Ru tryhidride complexes. 34 Even for the Cp t Bu 3 molecule, the Gibbs free energy diagram (Figure 7) shows that TS R1 has a lower energy than the H 2 complex. The energy of TS R1 is only above that of the H 2 complex (TS R1 = 2.65 kcal/ mol, H 2 complex = 2.64 kcal/mol) for the electronic energy.…”
Section: ■ Computational Detailsmentioning
confidence: 98%
“…These values correspond well with a recent theoretical report for a similar reaction in Ru tryhidride complexes. 34 Even for the Cp t Bu 3 molecule, the Gibbs free energy diagram (Figure 7) shows that TS R1 has a lower energy than the H 2 complex. The energy of TS R1 is only above that of the H 2 complex (TS R1 = 2.65 kcal/ mol, H 2 complex = 2.64 kcal/mol) for the electronic energy.…”
Section: ■ Computational Detailsmentioning
confidence: 98%
“…Participation of the metal atom in hydrogen bonding at a hydride site was shown to assist direct proton transfer to W and Os in the case of [Cp*WH 3 (dppe)] [21] (Cp* = h 5 -C 5 Me 5 ) and [Cp*OsH(dppe)] [22] (dppe = k 2 -Ph 2 PCH 2 CH 2 PPh 2 ). [21,26] Interestingly short metal-proton distance and significant Mo···HF overlap population were found in one of the first computational works on DHB [27] but were barely discussed. [24] For the [Cp*MH(dppe)] series, passing from ruthenium to osmium changes the reaction mechanism: proton transfer yields dihydrogen complex for Ru but cis-dihydride for Os.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that the methanol plays an important role in the stereoselectivity and the regeneration of the catalytically active copper species. The coordinated methanol has also been observed to exert important effects in other reactions catalyzed by this copper complex [19], as well as in other metal-mediated transformations of alkynes [20].…”
Section: Resultsmentioning
confidence: 99%